Resilience and Recovery of Albay’s Food Services in the Post-Pandemic EraAlbay Food Services: Post-Pandemic Recovery - Abrera, Jason L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The COVID-19 pandemic significantly disrupted the food services sector across the Philippines, with localized industries such as those in Albay Province facing unprecedented challenges. This study examines the recovery dynamics of Albay’s food services sector in the post-pandemic era using a descriptive quantitative approach. Business profiles were analyzed in terms of employee count, capital investment, and modes of operation (dine-in, take-out, delivery, catering), revealing a predominance of micro-enterprises (77.05%) and limited capital resources. Despite minimal government support, food service establishments demonstrated strong resilience through adaptive strategies, most notably, the adoption of advanced digital tools. The study found high uptake of e-commerce platforms (94.26%), online delivery systems (81.97%), and universal implementation of digital payments and marketing strategies (100%). Financial recovery was also bolstered by private loans (24.59%), primarily bank-based. Survey data indicate that businesses achieved full recovery across key dimensions including operational efficiency, customer loyalty, financial stability, and employee retention. These findings show the industry capacity for innovation and adaptation despite the institutional gaps. The study recommends for the continued investment in technology, instruction and assistance using digital tools, and improve online payment systems to sustain the growth and ensure preparedness against the future disruptions.